The Impact of Search Engine Optimization on The Visibility of Research Paper and Citations - Asim Shahzad; Nazri Mohd Nawi; Norhamreeza Abd Hamid; Sundas Naqeeb Khan; Muhammad Aamir; Arif Ullah; Salfarina Abdullah (JOIV : International Journal on Informatics Visualization, 2017)
The initial criteria for evaluating a researcher's output is the number of papers published. Furthermore, for the measurement of author's research quality, the number of citations is significant.  Typically, citations are directly linked with the visibility of a research paper. Many researches had shown that the visibility of a research paper can be improved further by using the search engine optimization techniques. In addition, some research already proved that the visibility of an article could improve the citation results. In this article, we analysed the impact of search engine optimization techniques that can improve the visibility of a research paper. Furthermore, this paper also proposing some strategies that can help and making the research publication visible to a large number of users.